A pré-escola no mundo digital: análise de percepções, práticas educativas e desafios de professores de uma escola em Bragança-Pará. - Gomes, Mara Fabiane Reis (My University, 2023)
This dissertation is linked to the Graduate Program in Education - University of Caxias do Sul. The general objective is to analyze perceptions, educational practices and challenges of preschool teachers of a school in Bragança-Pará in the use of Digital Information and Communication Technologies (ICTs). Specifically, to identify what perceptions of digital education the pre- school teachers of a school in Bragança have and how they have used TDICs in learning environments; to highlight the main challenges of preschool teachers of a school in Bragança for the use of TDICs at this stage of Early Childhood Education. This is a qualitative research of exploratory and descriptive character whose focus is anchored in a field study with the construction of a corpus from the transcription of interviews with semi structured questions. Therefore, an academic work, built with scientific rigor on a theme so emerging and necessary to the education of current times, and which imposes on its researchers a great theoretical immersion and a look at professional practices. The theoristswho underlie the researched theme and with whom we agree with the ideas; They are Ariès (1978), Lévy (1999), Fantin (2010), Moran (2012), Kenski (2013), among others. This action allowed the fruitful facilitation in the textual organization and thus emerged the categories of analysis of the data produced in the semi-structured interviews: Perception of the Teachers, Potentialities and motivation generated by the TDICs and Structure through which the data analysis and the configurations of inferences and organicity were made. The results pointed out that the teachers have somehow used the TDICs in the learning environments, the data brought us the understanding of the knowledge they have of the various possibilities arising from the use of TDICs in their practices, that is, the researched subjects point out the TDICs as allies in the educational process and the understanding of digital language as an indispensable field to the curriculum and teaching- learning of Early Childhood Education,however, paradoxically, they recognize challenges in relation to the use of TDICs in preschool, among them the lack of appropriation of these tools and their integration into educational routines and the lack of infrastructure of the school, the locus of the research. [resumo fornecido pelo autor]
Esta dissertação está vinculada ao Programa de Pós-Graduação em Educação - Universidade de Caxias do Sul. O objetivo geral consiste em analisar percepções, práticas educativas e desafios de professores da pré-escola de uma Escola em Bragança-Pará no uso das Tecnologias Digitais de Informação e Comunicação (TDICs). Especificamente, identificar quais percepções de educação digital tem os professores da pré-escola de uma Escola em Bragança e de que forma tem utilizado as TDICs nos ambientes de aprendizagens; evidenciar quais os principais desafios dos professores da pré-escola de uma Escola em Bragança para o uso TDICs nessa etapa da Educação Infantil. Trata-se de uma pesquisa do tipo qualitativa de caráter exploratório e descritivo cujo enfoque está ancorado em um estudo de campo com a construção de um corpus a partir da transcrição de entrevistas com perguntas semiestruturadas. Portanto, um trabalho acadêmico, construído com rigor científico sobre uma temática tão emergente e necessária à educação dos tempos atuais, e que impõe aos seus pesquisadores uma grandiosa imersão teórica e um olhar sobre as práticas profissionais. Os teóricos que fundamentam a temática pesquisada e com os quais coadunamos com as ideias; são, Ariès (1978), Lévy (1999), Fantin (2010), Moran (2012), Kenski (2013), entre outros. Essa ação permitiu a profícua facilitação na organização textual e assim emergiram as categorias de análise dos dados produzidos nas entrevistas semiestruturadas: Percepção das Professoras, Potencialidades e motivação gerada pelas TDICs e Estrutura por meio das quais fez-se a análise dos dados e as configurações de inferências e da organicidade. Os resultados apontaram que as professoras de alguma forma têm utilizado as TDICs nos ambientes deaprendizagens, os dados nos trouxeram a compreensão sobre o conhecimento que possuem das várias possibilidades oriundas da utilização das TDICs em suas práticas, ou seja, os sujeitos pesquisados apontam as TDICs como aliadas no processo educacional e a compreensão da linguagem digital como campo indispensável ao currículo e ao ensino aprendizagem da Educação Infantil, contudo, paradoxalmente, reconhecem, desafios em relação ao uso das TDICs na pré-escola, dentre eles a falta de apropriação dessas ferramentas e sua integração nas rotinas educacionais e a falta de infraestrutura da escola lócus da pesquisa. [resumo fornecido pelo autor]
Keywords: Educação pré-escolar; Educação de crianças; Tecnologia educacional; Professores de educação pré-escolar; Escolas públicas - Bragança (PA); Education, Preschool; Education of children; Educational technology; Preschool teachers; Public schools - Bragança (Brazil)